Efficacy and Safety of Various First-Line Therapeutic Strategies for Fetal Tachycardias: A Network Meta-Analysis and Systematic Review - Qin, Jiangwei; Deng, Zhengrong; Tang, Changqing; Zhang, Yunfan; Hu, Ruolan; Li, Jiawen; Hua, Yimin; Li, Yifei (Frontiers in Pharmacology, 2022)
Background: Fetal arrhythmias are common cardiac abnormalities associated with high mortality due to ventricular dysfunction and heart failure, particularly when accompanied by hydrops. Although several types of common fetal tachycardias have been relatively identified medications, such as digoxin, flecainide, and sotalol, there is no first-line drug treatment protocol established for the treatment of various types of fetal tachycardias. Methods: We conducted a network meta-analysis using a Bayesian hierarchical framework to obtain a model for integrating both direct and indirect evidence. All tachycardia types (Total group), supraventricular tachycardia (SVT subgroup), atrial flutter (AF subgroup), hydrops subgroup, and non-hydrops subgroup fetuses were analyzed, and five first-line regimens were ranked according to treatment outcomes: digoxin monotherapy (D), flecainide monotherapy (F), sotalol monotherapy (S), digoxin plus flecainide combination therapy (DF), and digoxin plus sotalol combination therapy (DS). Effectiveness and safety were determined according to the cardioversion rate and intrauterine death rate. Results: The pooled data indicated that DF combination therapy was always superior to D monotherapy, regardless of the tachycardia type or the presence of hydrops: Total, 2.44 (95% CrI: 1.59, 3.52); SVT, 2.77 (95% CrI: 1.59, 4.07); AF, 67.85 (95% CrI: 14.25, 168.68); hydrops, 6.03 (95% CrI: 2.54, 10.68); and non-hydrops, 5.06 (95% CrI: 1.87, 9.88). DF and F had a similar effect on control of fetal tachycardias. No significant differences were observed when comparing S, DS with D therapies across the subgroup analyses for the SVT, hydrops, and non-hydrops groups. No significant differences in mortality risks were among the various treatment regimens for the total group. And no significant differences were found in rates of intrauterine death rates at the same cardioversion amount. Conclusion The flecainide monotherapy and combination of digoxin and flecainide should be considered the most superior therapeutic strategies for fetal tachycardia. Systematic Review Registration: (https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=288997), identifier (288997).